Implementation of Accreditation-Based Graduate Quality Assurance in Private Schools - Hasanah, Enung; Afriliandhi, Cucu (JURNAL AL-TANZIM, 2023)
This study aims to analyze the implementation of accreditation-based graduate quality assurance at private junior high schools in Sleman, Yogyakarta Special Region. This research design is qualitative research. The subjects of this study consisted of school principals, deputy principals, teachers, employees, parents and students, who received an A accreditation rating. Data collection was carried out through in-depth individual interviews, observation and documentation. The study results a show that accreditation-based quality assurance on the graduate quality component is carried out by applying adaptive, contextualized, and cooperative principles. The results of this study imply that implementing school quality assurance is not just managing administration but requires the development of a state of mind from all stakeholders.